Opportunities and threats to contact lens practice: A global survey perspective. Issue 6 (December 2021) - Thite, Nilesh; Desiato, Alfredo; Shinde, Lakshmi; Wolffsohn, James S.; Naroo, Shehzad A.; Santodomingo-Rubido, Jacinto; Cho, Pauline; Jones, Debbie; Villa-Collar, César; Carrillo, Guillermo; Chan, Osbert; Wang, Haiying; et al.
Abstract: Aim: To understand the views of contact lens (CL) practitioners across the globe regarding what they perceive as opportunities and threats in CL practice. Methods: A self-administered anonymised questionnaire, constructed in English and translated in six more languages, was distributed through reputed international professional bodies and academic institutions worldwide. The questionnaire included items on demographic characteristics, type of practice, and questions designed to explore practitioners' perspective on the future of their CL practice over the next five years. Results: A total of 2408 valid responses were analysed. Multifocal CLs for presbyopia, CLs for myopia control, use of daily disposable (DD) CLs for occasional wear, and biocompatible materials to improve comfort were identified as promising areas of opportunities by practitioners (all 8/10). Respondents from North America, and Europe valued DDCLs for occasional wear moderately more favourable (Median: 9/10 for all) as compared to colleagues in Asia (Median: 8/10, p < 0.001), South America (Median: 8/10, p < 0.01), and Africa (Median: 8/10p < 0.01). Multifocal CLs for presbyopia was perceived as a better opportunity by practitioners in North America and Europe (Median: 9/10 for both), as well as in Australasia (Median: 8/10), in comparison to Asia, Africa, and Middle East (for all Median: 6/10, p < 0.001). Practitioners expressed concerns about the availability of CLs and CL prescriptions online without direct professional involvement (both 9/10). Conclusions: Overall, the most appealing opportunities for CL practice growth were identified in occasional use of DD CLs, biocompatible materials to reduce CL discomfort, multifocal CLs for presbyopia correction and management of myopia control with CLs. Lack of regulation in CL sales, especially online, seemed to be a constant threat. The insights from this study can be used to design targeted strategies to enhance CL practice across the globe and in specific geographical areas.